Identity Claims: Why Liberal Neutrality is the Solution, Not the Problem. (24th November 2013) - Balint, Peter
<x xml:space="preserve">Abstract</x> Almost all theories of multiculturalism (and similar differentiated rights) start by rejecting liberal state neutrality as unable adequately to address issues of diversity. In this article, I challenge this move and argue that neutrality has been wrongly characterised. Neutrality is an unrealisable yet still action‐guiding political ideal that is not absolute. It only makes sense in relation to a particular range of things (in this case, people's ways of life), and needs to be sensitive to the changing nature of this range. Unlike neutrality as 'benign neglect', this allows it to be sufficiently neutral over time to changing ways of life. Yet difference sensitivity can be realised by either withdrawing support for all parties or actively assisting them. In the last part of the article, I argue that state neutrality should involve withdrawing support for favoured ways of life rather than actively recognising the various ways of life and identities of its citizens.